The impact of support function on land reform delivery in the Department of Land Affairs in Limpopo Province - Mphahlele, R. V. (My University, 2005)
Refer to the abstract
Thesis (MPA.) --University of Limpopo, 2005
Keywords: Land reform; Service delivery; Land reform -- South Africa -- Limpopo.; Land reform -- Government policy -- South Africa -- Limpopo; Land use, Rural -- South Africa -- Limpopo; Land tenure -- South Africa -- Limpopo